Nacella kerguelenensis - González-Wevar, Claudio A.; Hüne, Mathias; Rosenfeld, Sebastián; Nakano, Tomoyuki; Saucède, Thomas; Spencer, Hamish; Poulin, Elie (Zenodo, 2018)
NACELLA KERGUELENENSIS (SMITH, 1879) (FIG. 10) Patella ( Patinella ) kerguelenensis Smith, 1879: 177, pl. 19, figs 13, 13a. Patella ( Nacella ) mytilina – 181, not of Helbling. Patella kerguelenensis – Watson, 1886: 27. Nacella kerguelenensis – Pilsbry, 1891: 121, pl. 49, figs 7, 8; Hedley, 1916: 44; Dell, 1964: 276; Powell, 1973: 192, pl. 173, figs 3, 4; Cantera & Arnaud, 1985: 33; González-Wevar et al. , 2010: 116; 2017: 862. Patinella kerguelenensis – Strebel, 1908: 83. Nacella mytilina – Thiele, 1912: 234, Powell, 1951: 80; 1973: 192 (in part, not of Helbling). Patinigera cf. kerguelenensis – Powell, 1955: 69. Patinigera kerguelenensis – Powell, 1957: 126. Nacella ( Patinigera ) mytilina – Cantera & Arnaud, 1985: 33 (not of Helbling) Nacella cf. mytilina – Troncoso et al. , 2001: 88 (not of Helbling). Material studied: Port-aux-Français, Kerguelen Islands (49°21’09.84’’ S, 70°13’05.89’’ E) N = 50; Port Christmas, Kerguelen Islands (48°41’40.22’’ S, 69°01’15.54’’ E) N = 60; Fjord des Portes Noires, Kerguelen Islands (49°29’47.32’’ S, 69°08’06.70’’ E) N = 50; Îles du Prince-de-Monaco, Kerguelen Islands (49°36’47.24’’ S, 69°14’11.38’’ E) N = 30; Baie des Cascades, Kerguelen Islands (49°10’02.31’’ S, 70°08’53.33’’ E) N = 30; Atlas Cove, Heard Island (53°01’27.99’’ S, 73°23’46.95’’ E) N = 10. Shell: The shell shape and sculpture are very variable in the species and two different morphotypes have been recorded at Kerguelen Islands: (1) a kelp-dweller (Fig. 10A) and (2) a hard-substrate morphotype (Fig. 10B, C). The shell and the sculpture of the hard-substrate morphotype are relatively constant in the analysed individuals, which exhibit a conical morphology, dorsally raised, with a very thick and non-translucent shell. The anterior part of the animal is laterally compressed (Fig. 10A–D). The shell is large (maximum length 120 mm) and has a medium profile. The apex is located at the the anterior 30% of the shell. All the slopes of the shell are convex. The aperture of the shell is oval. The surface of the ...